Correlation of vitamin D and E plasma levels with the pathophysiology of type 2 diabetes mellitus among adults in Selangor, Malaysia - Md Razip, Nurliyana Najwa (2018)
Poor glycemic status instigated by derangement of insulin signalling mechanism is the leading cause of Type 2 Diabetes Mellitus (T2DM) pathophysiology. Classical risk factors such as obesity, increasing age, sedentary lifestyle and metabolic syndromes have strong association with T2DM. Recent evidence indicates plasma level of vitamin D and E may alter insulin sensitivity to the cells, but its pathophysiology to diabetes remains unclear. The study was aimed to investigate the potential correlation of plasma level of vitamin D and E with glycemic status in T2DM pathophysiology. A cross-sectional study involved 50 DM and 50 non-DM respondents were recruited through convenient sampling. Socio-demographic, medical background, anthropometric measurement and lifestyle behaviours were the risk factors of diabetes and association of plasma level vitamin D and E were the new risk factors that proposed in the current study. SPSS version 22.0 was adopted for the statistical analysis and significant value was set at P<0.05. The outcome of study highlighted poor glycemic status in DM group (9.32±2.61%) with significant different with non-DM (6.67±2.01%) group. The association of poor glycemic status with gender, level of education, ethnicity and family history who is having diabetes were statistically significant (P<0.05) in DM group. Glycemic status [(haemoglobin A1c (HbA1c) and fasting blood glucose (FBG)] and lipid profiles status [high density lipoprotein (HDL), low density lipoprotein (LDL) and total cholesterol (TC)] were significantly different between DM and non-DM groups. Most of the respondent were deficient of plasma vitamin D with mean value 3.43±2.95 ng/mL in non-DM group and 4.44±5.86 ng/mL in DM group which accounted about 82% and 84% respondent in respective groups. Further bivariate analysis with the group of deficiency of vitamin D (<20 ng/mL) with glycemic status (<7% and >7% of HbA1c level) revealed strong association (P<0.05) of deficiency of vitamin D with poor glycemic status (HbA1c and FBG) in DM groups. Lipid profile status (LDL, HDL and TC) were significantly higher (P<0.05) in non-DM group. The calcium level in non-DM was 8.11 mg/dL and DM group was 9.57 mg/dL. Glycemic status (HbA1c, FBG and C-Peptide) and lipid profile status (LDL and HDL) were significantly associated (P<0.05) with calcium plasma level. The distribution of total vitamin E (VE) in plasma was evidently higher in DM group (4.9±4.3 μg/mL) compared to non-DM group (3.97±3.33 μg/mL). Furthermore, the relationship of total VE with deficiency of vitamin D has significantly associated in poor glycemic status (P<0.05) in DM group. At higher level of total VE (>4.9 μg/mL), there was poor glycemic status in DM group. Concurrently, lipid profiles status suggested LDL, HDL and TC were also significantly higher (P<0.05) in DM group at high level of total VE (>4.9 μg/mL). In conclusion, the present study suggested that predisposing of multiple risk factors of T2DM which predominate in poor glycemic status have strong association with deficiency of vitamin D and elevated plasma vitamin E amongst diabetic respondents. Thus, the elucidation of association of vitamin D and E in current study define the involvement of vitamin D in insulin signalling and the role of vitamin E in quenching free radical which both are interplay in T2DM pathophysiology.